Sixkiller, U.S. Marshal : day of rage - Johnstone, William W.; Johnstone, J. A. (Sixkiller: US Marshal, 2016)
"It was there for the taking: $75,000 in gold bullion, the combined payrolls of three productive gold mines, just waiting to be stolen from under the noses of a bickering sheriff and city marshal. Billy Ray Gilmore and his band of kill-crazy outlaws have a plan to do it, too--that is, until Sixkiller comes to town. Hiding his badge to conceal his identity as a U.S. marshal, Sixkiller goes undercover to smoke out the culprits before they strike. But in this town full of two-legged rattlesnakes, deadly surprises lurk behind every saloon door. To keep from being bitten, Sixkiller will have to lay a few traps of his own. Lucky for him, what this town lack sin law, it makes up for in guns--and dynamite."--Page [4] cover.